The Effect of Transformational Leadership and Work Discipline Against The Employee Performance With Turnover Intention as The Intervening Variable - Paijan Paijan (Universitas Mercu Buana, 2022)
This study is to analyze the effect of transformational leadership, work discipline against the employee performance with turnover intention as the intervening variabel. The object of this research is the employees of PT. Prima Utama. This research was conducted on 270 respondents by using a quantitative descriptive approach. The determination of the sample size is using the Slovin formula so that the sample used is 161 respondents. Methods of data collection using survey methods, with the research instrument is using a questionnaire. The research method in this research is using Structural Equation Model (SEM). This study has stated that transformational leadership has a negative and significant effect on turnover intention. Work discipline has a negative and significant effect on turnover intention. Turnover intention has a negative and significant effect on employee performance. Transformational leadership has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance.